Phenolic content and antioxidant activity of hydromethanolic and aqueous extracts of aerial parts of Phlomis crinita. - Ismahane Derafa; Smain Amira; Fatima Benchikh; Walid Mamache; Chahrazed Kaoudoune (Turkish Journal of Agriculture: Food Science and Technology)
Phlomis crinita is a plant species of the family Lamiaceae including more than 100 perennial herbs, shrubs, and sub-shrubs species native to the Mediterranean, Central Asia, and India. This species is commonly a good natural source of various secondary metabolites. Therefore, the present study was conducted to determine phenolic content and antioxidant activity of hydromethanolic (PC ME) and aqueous extracts (PC AQE) of aerial parts of P. crinita. Total polyphenols, flavonoids and tannins were quantified, respectively by the methods of Folin-Ciocalteu reagent, aluminum trichloride (AlCl3) and Bate-Smith method. The in vitro antioxidant activity was assessed using DPPH and ABTS•+ radical scavenging, β-carotene-linoleic acid, reducing power and ferrous ion chelating activity assays. PC ME showed high level of tannins (132,13 ±0.68 µg TAE/mg extract) and total phenolic content (82.71±0.79 µg GAE/mg extract), in addition a marked inhibiting oxidation activity of β-carotene/ linoleic acid (74.10%) was observed. Results showed also a higher iron-chelating activity of PC ME (0.20 mg/mL) compared to PC AQE (0.046 mg/mL). The plant extracts revealed a significant antioxidant activity as evidenced by the DPPH and ABTS radical scavenging activity (IC50 = 0.103 mg/mL for PC ME and 0.144 mg/mL for PC AQE) for DPPH assay and (IC50 = 0.0130 mg/mL for PC ME and 0.0187 mg/mL for PC AQE) , as well as the PC ME exhibits higher reducing power (IC50 =0.288mg/mL) than PC AQE (0.296 mg/mL). As a result, P.crinita is suggested as a promising and effective therapeutic medicinal plant for the treatment of several diseases.